COMPARE MORPHOLOGICAL AND PHYSIOLOGICAL TRAITS OF NATIVE PEAR GENOTYPES OF SARDASHT CITY : Life Science - Plant Sciences - ALIPOOR , FEREIDOON (International Journal of Life Science and Pharma Research, 2017)
According to findings of researchers the west of Iran is part of the center of origin pear fruit and the West Azerbaijan province, according to the topographical status and geographical conditions, its vegetation has great diversity. Native Pear in this province, especially in the highlands and jungles of Sardasht city as types of wild pear has a great variety. Accordingly, compare of the morphological and physiological traits of native pear of Sardasht based on national guideline tests for distinctness, uniformity, and stability (DUS )was conducted. There were, respectively 5and 9 traits of the shape of trees and one-year branch, among morphological traits and among physiological traits which 15 traits related to fruit, were investigated. This research, all genotype kinds of native pear, after identifying the trees and coding them was done in two stages and the considered traits were written and in a stage in the laboratory the chemical traits studied and statistical investigations were done using SPSS software. Chart analysis and resulted cluster analysis showed the number of 8 types of native pear genotype and showed its close relative value. In general, according to variance analysis of biochemical traits, the correlation was observed between all traits that most of the trees had abundant diversity. The collection of key traits was, well able to make differentiation and distinction between various native pear trees of Sardasht area.